Addition of a surfactant to water increases the acaricidal activity of extracts of some plant species used to control ticks by Zimbabwean smallholder farmers - Nyahangare, Emmanuel T. (BMC Vet Res, 2019)
BACKGROUND: Many studies have revealed that bioactive compounds for different indications are not extracted from plants with water, the only extractant practically available to rural communities. We compared the acaricidal activity of acetone extracts of 13 species used traditionally to protect cattle against ticks. We also investigated if the extraction of biologically active compounds against Rhipicephalus (Boophilus) decoloratus ticks could be enhanced by adding a liquid soap that is locally available to smallholder farmers. METHODS: A total of 13 plant species selected based on reported traditional use in Zimbabwe, were dried and finely ground before extraction with water, or water plus a surfactant, or acetone. The adapted Shaw Larval Immersion Test (SLIT) method was used to determine the activity of acetone and crude water extracts with or without liquid soap against the tick larvae. The activity of four fractions of crude acetone extracts (extracted using solvents of different polarity), of the most active plant species, Maerua edulis (tuber and leaf) was also compared to identify the most active fraction. RESULTS: Aqueous plant extracts were not toxic to ticks, but the addition of 1% liquid soap as a surfactant increased mortality of the R. (B) decoloratus larvae significantly. With the Maerua edulis tuber extract, the efficacy of the 1% liquid soap was comparable to that of the amitraz based commercial synthetic acaricide. The use of acetone as an extractant, also increased the mortality of the tick larvae in all the plant species. With M. edulis (tuber and leaf), Monadenium lugardae and Kleinia sp. acetone extracts, the activity was comparable to that of the positive control (a commercially available amitraz-based synthetic acaricide). The non-polar fractions of the acetone extract of leaf and tuber of M. edulis caused up to 100% mortality. This indicates that non-polar to intermediate polarity compounds are responsible for the acaricidal activity. CONCLUSION: Organic solvents such as acetone extracted active compounds but water did not. By adding commonly available dishwashing soap to water active compounds were extracted leading to a high acaricidal activity of the plant extracts. In some cases, it was as active as non-polar extracts and a synthetic commercial acaricide (positive control). This approach makes it possible for the smallholder farmers and traditional healers to extract biologically active compounds from plants by using water.